Cyber-security in smart cities: The case of Dubai - Marios-Panagiotis Efthymiopoulos (Journal of Innovation and Entrepreneurship, 2016)
The city of Dubai emerges as a leading partner in not only technology innovation but also designed infrastructure and strategic security. There is a strategy, which will globally add the city and leadership to the leading smart cities of the world. Considering current and future challenges, the strategic aim is to "smart" wire the city of Dubai by 2020. Dubai is a city of strategic technology, innovation and management. It is a global, vibrant and emerging economy among others, that can become an economic hub of the MENA (Middle East and North Africa) region. The aim of this paper is to explore, analyze, and discuss elements of strategic management, innovation, development. It is also the aim to discuss elements of strategic security, in making the city is cyber-secure in a smart networked infrastructural and service provider, environment.
Keywords: 650; Cyber-security; Development; Democracy; Smart cities; Infrastructure; Dubai; Dubai model; Expo 2020; Strategic planning